The Politics of Family Cohesion in the Gulf: Islamic authority, new media, and the logic of the modern rentier state - Alexandre Caeiro (Arabian Humanities)
This article explores the politics of family cohesion in a Muslim polity simultaneously committed to the application of Islamic law, the preservation of cultural identity, and socio‑economic modernization. The article focuses on the work of Qatar’s Ministry of Endowments and Islamic Affairs, a government body that seeks to make Wahhābī Islam relevant to a society in the midst of rapid social change. Drawing on an analysis of the Ministry’s fatwas on family life, the article shows how Qatar’s media muftis have incorporated modern assumptions into their discourse and adjusted to new power configurations. The dissonance between the discourses articulated within official religious institutions and those found in other state bodies reflects the growing polarization of Qatari society, the normative pluralism undergirding modernization in the Gulf, and the regulatory ambitions of proliferating state institutions in a rentier economy.